A clinical analysis of hemophagocytic syndrome secondary to autoimmune diseases - Yang Liu,; Qian Li,; Yazhen Su,; Guozhu Che,; Ying Liu,; Pengyan Qiao,; Sumiao Liu,; Ke Xu, (Archives of Rheumatology, 2023)
Objectives: This study aimed to analyze the differences of etiologies and clinical features between patients with autoimmune-associated hemophagocytic syndrome (AAHS) and those with other underlying diseases of hemophagocytic syndrome (HPS). Patients and methods: The retrospective study was performed with 130 HPS patients (70 males, 60 females; mean age: 50.4±18.1 years; range, 13 to 85 years) between January 1st, 2011, and April 1st, 2022. The patients fulfilled at least five of the eight criteria proposed by the Histiocytosis Society in 2004. The underlying diseases related to HPS were divided into four categories: autoimmune, infection, malignancy and idiopathic diseases. And the clinical manifestations, laboratory examinations, treatments, and prognosis were analyzed respectively. Results: Nineteen (14.6%) patients had AAHS, 45 (34.6%) had infection-associated HPS, 57 (43.8%) had malignancy-associated HPS, and nine (6.9%) had idiopathic HPS. The most common symptoms of HPS were unremitting fever in 123 (94.6%) of 130 patients and splenomegaly in 92 (70.8%). All patients manifested a decline of at least two lineages of hematopoietic cells. The absolute values of T cells and B cells of AAHS were significantly higher than that of malignancy-associated HPS. The levels of soluble CD25 (interleukin-2 receptor) of AAHS were the lowest among all-cause HPS (p<0.05). The all-cause mortality rate of hospitalized patients with HPS was 46.2%. The patients with AAHS had a better prognosis compared to other etiologies (odds ratio [OR]=0.091, 95% confidence interval [CI]: 0.011-0.775, p=0.028). Epstein-Barr virus infection (OR=4.761, 95% CI: 1.619-14.004, p=0.005) and pulmonary involvement (OR=4.555 95% CI: 1.524-13.609, p=0.007) were independent predictors of poor outcome in HPS. Thrombocytopenia (OR=0.978, 95% CI: 0.968-0.999, p=0.040) had a boundary effect on prognosis. Conclusion: Patients with HPS secondary to autoimmune disease have better outcomes compared to patients complicated with Epstein-Barr virus infection or pulmonary involvement.